Prognostic Value of Basic Fibroblast Growth Factor (bFGF) in Lung Cancer: A Systematic Review with Meta-Analysis. - Mingming Hu; Ying Hu; Jiabei He; Baolan Li (PLoS ONE, 2016)
Background Basic fibroblast growth factor (bFGF) is known to stimulate angiogenesis and thus to influence the proliferation, migration and survival of tumor cells. Many studies examined the relationship between human bFGF overexpression and survival in lung cancer patients, but the results have been mixed. To systematically summarize the clinical prognostic function of bFGF in lung cancer, we performed this systematic review with meta-analysis. Method Studies were identified by an electronic search of PubMed, EMBASE, China National Knowledge Infrastructure and Wanfang databases, including publications prior to August 2014. Pooled hazard ratios (HR) for overall survival (OS) were aggregated and quantitatively analyzed by meta-analysis. Results Twenty-two studies (n = 2154) were evaluated in the meta-analysis. Combined HR suggested that bFGF overexpression had an adverse impact on survival of patients with lung cancer(HR = 1.202,95%CI, 1.022-1.382). Our subgroup analysis revealed that the combined HR evaluating bFGF expression on OS in operable non-small cell lung cancer (NSCLC) was 1.553 (95%CI, 1.120-1.986); the combined HR in small cell lung cancer (SCLC) was 1.667 (95%CI, 1.035-2.299). There was no significant impact of bFGF expression on survival in advanced NSCLC. Conclusion This meta-analysis showed that bFGF overexpression is a potential indicator of worse prognosis for patients with operable NSCLC and SCLC, but is not associated with outcome in advanced NSCLC. The data suggests that high bFGF expression is highly related to poor prognosis. Nevertheless,more high-quality studies should be performed in order to provide additional evidence for the prognostic value of bFGF in lung cancer.